Impact of COVID-19 Pandemic on Mutual Fund Flows : Evidence from the Indian Mutual Fund Industry - Yadav, Ajay Pratap; Yadav, Ratnesh Kumar (Indian Journal of Research in Capital Markets, 2024)
Purpose : The objective of the study was to analyze the changing patterns in terms of systematic investment plans (SIP) investments, net inflow/outflow, and asset under management (AUM) of the Indian mutual fund industry. The study aimed to determine whether there had been noticeable changes in investment patterns AUM before COVID and during/post-COVID period across different investors and investment categories. Methodology : While following descriptive research, data related to SIPs, net inflows as per scheme structure, aggregate AUM as per investment objectives, and investments in schemes (AUM) by different categories of investors were bifurcated into two segments. The first segment was concerned with pre-COVID duration, spanning October–December 2017 to October–December 2019. The second segment covered during/post-COVID, January–March 2020 to January–March 2022. A t-test was applied to examine the mean differences. Findings : Only HNI investors increased their investment in all schemes during the COVID-19 pandemic. Retail investors boosted their shareholding in all schemes except debt-oriented ones. Except for HNIs and retail investors, the average AUM of banks and FIIs declined in equity-oriented schemes. However, corporate investors boosted their investments in all categories except gilt and equity-oriented schemes. Practical Implication : Reasons for contradicting investment patterns exhibited by retail investors, HNIs, banks, and FIIs during the pre-COVID and COVID periods could be further explored by the managers to know the underlying reasons and act accordingly in such scenarios. Furthermore, mutual fund flows during the pandemic also indicated market sentiments. The investors and managers could use such changes in flows to make informed decisions.